Principal Leadership in Improving Educational Quality: A Case of SD Gugus VI Geumpang, Pidie Regency - Hadi, Abdul; Yuhrizal, Yuhrizal; Bahrun, Bahrun (Jurnal Pendidikan Progresif, 2021)
The purpose of this study was: to find out: the programs, strategies, and constraints faced by school principals in improving the quality of education in the Elementary School in Cluster VI of Geumpang Geumpang Pidie Regency. This study uses a descriptive method with a qualitative approach. Data collection techniques used are: interviews, observation, and documentation studies. The research subjects were: school principals, vice principals, and teachers. The results showed that: (1) The planning of the principal’s program in improving the quality of education has been prepared, but is not well detailed, (2) Implementation of education quality improvement programs by implementing democratic leadership strategies. In facing teachers, principals often exchange ideas with teachers, so find an effective way to improve their performance in the development of the learning process, and (3) The obstacles encountered by principals in improving the quality of education include: lack of available funds for teacher training outside official hours, there are still teachers who are less active, and the results of upgrading have not been able to be socialized to their friends.Keywords: principal leadership, educational quality, elementary school.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202108